2022
DOI: 10.1002/cnm.3646
|View full text |Cite
|
Sign up to set email alerts
|

Computational biomechanics of human knee joint in stair ascent: Muscle‐ligament‐contact forces and comparison with level walking

Abstract: About a third of knee joint disorders originate from the patellofemoral (PF) site that makes stair ascent a difficult activity for patients. A detailed finite element model of the knee joint is coupled to a lower extremity musculoskeletal model to simulate the stance phase of stair ascent. It is driven by the mean of measurements on the hip-knee-ankle moments-angles as well as ground reaction forces reported in healthy individuals. Predicted muscle activities compare well to the recorded electromyography data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Such realistic simulation of passive-active coupling is possible only when both components are accurately represented alongside in a model study. The coupled model of the lower extremity for the knee (Makani et al, 2022; Sharifi and Shirazi-Adl, 2021) and hip (Hua et al, 2022) attest to this point.…”
Section: Discussionmentioning
confidence: 64%
“…Such realistic simulation of passive-active coupling is possible only when both components are accurately represented alongside in a model study. The coupled model of the lower extremity for the knee (Makani et al, 2022; Sharifi and Shirazi-Adl, 2021) and hip (Hua et al, 2022) attest to this point.…”
Section: Discussionmentioning
confidence: 64%
“…6,27 Importantly, the increased knee EMS not only signifies a localized impact on muscular performance but also may have an impact on overall joint stability and functionality. 28 Strengthened knee extensor muscles could contribute to enhanced joint support and a reduction in mechanical stress on the affected knee joint, 20,22 potentially translating into improved activity levels and symptom relief for individuals with mild knee OA. 27 Notably, in this study, we also found a significant decrease in knee EMS in female nonwalkers and male nonwalkers at 24 mos compared with baseline.…”
Section: Discussionmentioning
confidence: 99%
“…This may potentially exacerbate the loss of medial knee cartilage and worsening of medial bone marrow lesions 18,19 . Nevertheless, studies have also highlighted the positive effects of strengthening extensor muscles, particularly the quadriceps, which could minimize the adverse consequences of HKA angle abnormalities 20,21 . By increasing EMS, the increased medial knee contact force caused by the increased HKA angle could be reduced, 20 thereby improving the medial JSN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation